A RELIGIÃO NO CONFLITO ENTRE ISRAEL E PALESTINA NO CONTEXTO DA CRIAÇÃO DO ESTADO JUDAICO: ASPECTOS HISTÓRICOS (1896-1948) - PRAZERES, TAMIRES SILVA PEREIRA (2016)
This search examines the religion in the conflict between Israel and Palestine, especially in the context of implementation of the State of Israel in 1948. The analysis takes as historical definition of conflict the period 1896-1948, when the inmigration of the first groups of Jews to the Palestinian territories. The initial question is how Jews and Muslims were related in the early years of inmigration to the creation of the State of Israel. The main issue to be clarified is how Western cultural building toward the Palestinians interfered in the conflict, especially with regard to the taking of the land and the construction of a new country within an existing, socially, religiously and culturally. Finally, the search asks about the effect of the conflict between Israelis and Palestinians in the Protestant religious space, especially among conservative groups and fundamentalists of this branch of christianity. The research is fully literature and refers to postcolonial theories to discuss the history of the territory, with regard to the religious aspects of the conflict